2023
DOI: 10.1002/mhs2.16
|View full text |Cite
|
Sign up to set email alerts
|

Strong mind, strong body: The promise of mind–body interventions to address growing mental health needs among youth

Abstract: As the prevalence of childhood and adolescent anxiety, depression, and other mental health concerns continues to rise, there has been an unprecedented increase in support of mind-body practices like yoga, dance, meditation, mindfulness, aerobic exercise, and more-in part driven by the mental health burden imposed by the COVID-19 pandemic.While a growing body of evidence supports the safety and effectiveness of mind-body approaches, gaps in funding for and empirical research on mechanistic underpinnings, method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…In school or medical settings, for instance, brief screenings may utilize type of trauma exposure as a risk factor to triage youth who may require follow-up screenings or information regarding how to access additional services. Though traditional mental healthcare systems still often require individuals to meet certain symptom thresholds, leveraging greater insight into the risk associated with specific trauma types may guide prevention efforts, as well as the allocation of alternative interventions, such as art and movement therapies—the efficacy of which has been recently demonstrated within refugee youth populations (Grasser et al, 2019; Grasser & Marusak, 2023). Additionally, the current findings imply that clinical work must move beyond counting the number of traumatic events and toward a deeper understanding of the effects of specific trauma experiences—which may also vary in regard to personal meaning and subjective interpretation for exposed youth.…”
Section: Discussionmentioning
confidence: 99%
“…In school or medical settings, for instance, brief screenings may utilize type of trauma exposure as a risk factor to triage youth who may require follow-up screenings or information regarding how to access additional services. Though traditional mental healthcare systems still often require individuals to meet certain symptom thresholds, leveraging greater insight into the risk associated with specific trauma types may guide prevention efforts, as well as the allocation of alternative interventions, such as art and movement therapies—the efficacy of which has been recently demonstrated within refugee youth populations (Grasser et al, 2019; Grasser & Marusak, 2023). Additionally, the current findings imply that clinical work must move beyond counting the number of traumatic events and toward a deeper understanding of the effects of specific trauma experiences—which may also vary in regard to personal meaning and subjective interpretation for exposed youth.…”
Section: Discussionmentioning
confidence: 99%
“…To date, various putative mechanisms are discussed, which involve changes in autonomic activity [28,29]. In sum, OMT and MBI were shown to improve MP [23,24], which may involve autonomic mechanisms [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…However, although OMT and MBI seem to improve MP, the underlying mechanisms are not fully understood [25,27]. To date, various putative mechanisms are discussed, which involve changes in autonomic activity [28,29]. In sum, OMT and MBI were shown to improve MP [23,24], which may involve autonomic mechanisms [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews have identified an average prevalence of depressive symptoms of 27% [7] and anxiety symptoms ranging from 11-80% depending on the chronic physical condition under evaluation [8]. With increasing recognition of the role of non-pharmacological options in the management of mental health symptoms, there have been a number of studies [9][10][11][12] supporting the impact of mind-body wellness techniques as effective management strategies [13]. Mind-body wellness is "an approach that focuses on the interactions among the brain, mind, body and behavior" [14].…”
Section: Introductionmentioning
confidence: 99%